Antimicrobial Resistance Glides in the Sky—Free-Living Birds as a Reservoir of Resistant Escherichia coli With Zoonotic Potential - Skarżyńska, Magdalena; Zaja̧c, Magdalena; Bomba, Arkadiusz; Bocian, Łukasz; Kozdruń, Wojciech; Polak, Marcin; Wia̧cek, Jarosław; Wasyl, Dariusz (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is one of the most important global health concerns, therefore the identification of AMR reservoirs and vectors is essential. The attention should be paid to the recognition of potential hazards associated with wildlife as this field still seems to be incompletely recognized. In this context, the role of free-living birds as AMR carriers is noteworthy. Therefore, we applied methods used in AMR monitoring, supplemented by colistin resistance screening to investigate the AMR status of Escherichia coli from free-living birds coming from the natural habitats and rescue centres. Whole-Genome Sequencing (WGS) of strains enabled to determine resistance mechanisms, investigate their epidemiological relationships and virulence potential. As far as we know, this study is one of the few that applied WGS of that number (n=71) of strains coming from wild avian reservoir. The primary concerns arising from our study relate to microbiological resistance and its determinants towards antimicrobial classes of the highest priority for the treatment of critical infections in people, e.g. cephalosporins, quinolones, polymyxins, aminoglycosides as well as fosfomycin. Among numerous determinants blaCTX-M-15, blaCMY-2, blaSHV-12, blaTEM-1B, qnrS1, qnrB19, mcr-1, fosA7, aac(3)-IIa, ant(3'')-Ia, aph(6)-Id and chromosomal gyrA, parC, parE mutations were identified. Fifty-two sequence types (STs) noted among 71 E. coli included global lineages: ST131, ST10, ST224 as well as three novel ST: 11104, 11105, and 11194. Numerous virulence factors were noted with the prevailing terC, gad, ompT, iss, traT, lpfA, and sitA. Single E. coli was Shiga-toxin producing. Our study shows that clonal spread of public and animal health relevance E. coli lineages is a serious avian associated hazard.